Harnessing and Improving the Nutrient Contents of Eepa (Left Over Pounded Yam) as a Way of Tackling Malnutrition among School Aged Children in Ifelodun Local Government Area of Kwara State, Nigeria (International Journal of Natural Sciences Research, 2022)
Access to an adequate diet is a key criterion for tackling malnutrition in school aged children. The aim of the study was to improve locally produced eepa as a way of tackling malnutrition among school aged children in Ifelodun local government area of Kwara State, Nigeria. The research designs used were survey method and complete randomized design. Purposive random sampling was used to select three communities from the study area. The study was conducted with a sample of 30 mothers and 300 school aged children from the three communities selected. Collection of data from pupils was obtained through a designed interview tool and questionnaire was given to mothers. The eepa diets were sent to the laboratory to determine the proximate, mineral composition and vitamin content of the eepa diets using AOAC 2019. All descriptive statistical analyses were performed with SPSS, version 12.0 for Windows while the laboratory data were subjected to analysis of variance (ANOVA) and means separated with Duncan Multiple Range Test (DMRT) using SAS. The results show that the locally produced diets had the highest percentage carbohydrate (35.60%) and caloric value (819.58kj/100). However three improved diets of eepa had the higher percentage ash, percentage lipids, percentage crude protein and percentage crude fibre, Ca, Mg, P, K, Na, vitamin B1, B2 B3 and vitamin C than the locally produced eepa. The new improved eepa diets were eepa- beans, eepa-locust beans + mushroom and eepa-fish. These three new improved eepa diets are more nutritious than the locally produced eepa.